The Impact of Fertilizer Use on Fruit Farmers' Productivity in Umbulsari Village - Firmanda, Bagus Aldio; Syarofi, Muhammad (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to explore the impact of fertilizer use on fruit farmers' productivity in Umbulsari Village. Both organic and inorganic fertilizers play a crucial role in enhancing fruit production, such as mangoes and oranges. The study adopts a quantitative approach with a descriptive method. Data was collected through a questionnaire distributed to 61 respondents selected using simple random sampling. Data analysis was performed using the Partial Least Squares (PLS) model through SmartPLS 3.0 software. The results reveal that fertilizer use has a significant and positive impact on farmers' productivity, with a T-statistic value of 203.317 and a P-value of 0.000. This study emphasizes the importance of using appropriate fertilizers to improve crop yields and the welfare of farmers.